ANALISIS KUALITAS KEHIDUPAN KERJA PERAWAT PELAKSANA DI RUMAH SAKIT PUTRI HIJAU MEDAN - Muchti Yuda Pratama, S.Psi., M.Kes (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2016)
ABSTRAK  Quality of work life is a problem that should get attention from the Putri Hijau Hospital Medan. This refers to the idea that the quality of work life is considered capable of increasing the participation and contribution of the executor nurses to the hospital. This type of research is descriptive with survey method that aims to analyze the quality of work life that is employee involvement, career development, problem solving, communication, available facilities, job security, workplace safety, balanced compensation, and pride of institution. This research was conducted at Putri Hijau Hospital Medan. The subjects of this study were 79 nurses who had D3 and S1 graduated nursing. Data analysis was performed using univariate analysis. It is suggested to the management of Putri Hijau Medan Hospital to pay more attention to the implementing nurses on problem solving, communication, available facilities, job security, and safety of work environment such as: giving opportunity to nurse executor to solve problems related to their work, regular meetings, holding counseling programs and recreational programs, scheduling official arrangements, and providing job security guarantees for implementing nurses. Keywords: Nurse Executor, Quality of Work Life, Hospital